A dohánytripsz egyedszámváltozását befolyásoló tényezők a nyírségi és kunadacsi dohányültetvényekben - Orosz, Szilvia; Bujdos, László; Varga, Lajos; Fekete, Tibor (GEORGIKON FOR AGRICULTURE, 2017)
Studies were conducted in 2015 and 2016 with yellow sticky traps in seven tobacco plantations. The purpose was to determine when and in what numbers onion thrips individuals can settle into tobacco plantations. The primary objective of the study was to determine the proper timing of chemical treatments, furthermore, the determination of crucial factors that can influence the population dynamics of T. tabaci.